Induced mutagenic frequency and spectrum of chlorophyll mutants in French bean - Mahamune, S E; Kothekar, V S (International Multidisciplinary Research Journal, 2012)
M2 generation was raised from EMS, SA and gamma ray treated M1 seeds of French bean varieties Varun and Waghya. M2 generation was screened for the frequency and spectrum of chlorophyll mutations. Chemical mutagens appeared to be more effective in inducing maximum frequencies than physical mutagen in both the varieties. 0.020% concentration of SA induced the highest frequency of chlorophyll mutants in Varun (9.47%) and Waghya (8.29%). Broad spectrum of chlorophyll mutants was recorded in M2 generation. Different chlorophyll mutants obtained in present investigation such as albina, xantha, chlorina and viridis revealed diversity in their frequencies in both the varieties. The spectrum of chlorophyll mutants in both the varieties indicated the dominance of chlorina and viridis mutants as compared to albina and xantha.